2009
DOI: 10.1091/mbc.e08-07-0732
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic K-Ras Regulates Proliferation and Cell Junctions in Lung Epithelial Cells through Induction of Cyclooxygenase-2 and Activation of Metalloproteinase-9

Abstract: Expression of oncogenic K-Ras is frequently observed in non-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…[40][41][42] These mutations also appear to be common to human non-small cell lung carcinoma. 43 It has also been observed that A549 cells are quite susceptible to undergoing senescence when treated with bone morphogenetic protein BMP4, which is one of the subgroups of the transforming growth factor-β (TGF-β) protein superfamily. 44 Therefore, it is possible that this type of cancer, which is the most common of the lung cancer types, may be particularly sensitive to therapy that is designed to induce senescence in tumor cells.…”
Section: Methodsmentioning
confidence: 99%
“…[40][41][42] These mutations also appear to be common to human non-small cell lung carcinoma. 43 It has also been observed that A549 cells are quite susceptible to undergoing senescence when treated with bone morphogenetic protein BMP4, which is one of the subgroups of the transforming growth factor-β (TGF-β) protein superfamily. 44 Therefore, it is possible that this type of cancer, which is the most common of the lung cancer types, may be particularly sensitive to therapy that is designed to induce senescence in tumor cells.…”
Section: Methodsmentioning
confidence: 99%
“…The primers employed were (substitution is shown underlined): forward, 5Ј-CTGGCCGCTGTC-TCCTGCAAGGCTTTCGACCT-CTTCCACTTTC-3Ј and reverse, 5Ј-GAAAGTGGAAGAGGTCG-AAAGCCTTGCAGGAGACAG-CGGCCAG-3Ј. The luciferase activity was measured in IMCD3 cells using the Luciferase Assay System (Promega, Madison, WI) according to the manufacturer's instructions and as described previously (32). Briefly, IMCD3 cells in six-well plates grown to 50% confluence were transiently transfected with each construct and a ␤-galactosidase reporter (used for normalizing the transfection efficiency).…”
Section: Methodsmentioning
confidence: 99%
“…3, less b-catenin protein expression was detected in sFRP1-expressing xenografts compared with mock counterparts. Furthermore, we checked the expression of cyclin D1 [8,26] and MMPs [27][28][29], downstream effector genes of b-catenin signaling, which are known to be involved in cell proliferation and spread, respectively. Concomitant with reduced expression of b-catenin, cyclin D1 and MMP-2 protein levels were considerably decreased in sFRP1-expressing tumors.…”
Section: Sfrp1 Restoration Alters B-catenin Signalingmentioning
confidence: 99%